Journalism Models in Western Democracies and the International Arena: The Case of the 2016 Failed Coup Attempt in Turkey - Fracchiolla, Domenico (PARTECIPAZIONE E CONFLITTO, 2020)
This paper explores the complex relationship between media and political systems in the context of the International News Flow, regarding the interdisciplinary research area between media study and International Relations. The focus is on International News Flow interactions and effects upon democratic political systems. The aim is to fill the gap concerning international relations in comparative media analysis literature. Despite using Hallin and Mancini’s framework (2004, 2012), the present research does not only apply their typology to test its validity, but it also applies the main International Relations theoretical frameworks that deepen the relationship between media and political systems to shed light on the degree of superimposition between structure-based and content-based frameworks of media systems. The case study is the 2016 failed military coup in Turkey. In particular, in terms of coverage and analysis, the study considers how the newspapers of four countries (Italy, France, Germany and England), which represent the three democracy models of Hallini and Mancini – Mediterranean, Liberal, Corporative plus one that cuts across different models – framed the failed coup attempt in the days following the beginning of the crisis.